Soluble PD1 levels are increased with disease activity in paediatric onset autoimmune hepatitis and inflammatory bowel disease - Timothy Hadley; Scott Gillespie; Hillary Espinoza; Jarod Prince; Henning Gronbaek; Shanmuganathan Chandrakasan; Subra Kuguthasan; Vasantha L. Kolachala; Nitika A. Gupta (Taylor & Francis Group, 2020)
Introduction: Immune mediated liver diseases entail a broad category which are associated with increased morbidity and mortality amongst the paediatric population. Programmed Death 1 (PD1) is an inhibitory receptor mainly expressed by T cells, and when activated shed into plasma as soluble PD1(sPD1). The AIM of this study was to evaluate sPD1 levels in plasma of paediatric patients with Autoimmune Hepatitis (AIH), Primary Sclerosing Cholangitis (PSC), AIH and PSC overlap, Inflammatory Bowel Disease (IBD) alone, and concurrent PSC/IBD and AIH/IBD in order to identify a biomarker to response or predict relapse verses remission. Methods: Plasma samples were collected from 41 paediatric patients. AIH patients were further categorized into active, incomplete responders and responders, based on response to standard therapy. sPD1 levels were measured and compared between PSC, PSC/AIH, IBD alone, PSC/IBD and AIH/IBD patients and between active AIH, incomplete responders and responders. Flow cytometry was performed to further analyze CD45RA+, CD3CD4, CD8, CCR7, CXCR3, CD38 and PD1. Results: In the AIH group, those with active disease demonstrated a significantly higher sPD1 levels in comparison to responders (*p > .001). However, the incomplete responders didn't show a reduction in sPD1 in comparison to active AIH and patients with IBD alone. Interestingly, patients with PSC showed significantly lower level of sPD1 compared to active AIH (*p < .002), whereas, patients with PSC in conjunction with AIH (*p < .006) or IBD (*p < .02) demonstrated a significant increase in sPD1. In addition, we have observed increased levels of circulating CD4 and CD8 bound PD1 in active AIH but not in PSC or responders suggesting T cells activation. CD4+ PD1 double positive cells demonstrated increased expression of CXCR3. Thus, suggesting the activation of PD1 + T cells is mediating through CXCR3 in Autoimmune hepatitis. Conclusions: Our study demonstrates that sPD1 levels correlate with active disease state of AIH and IBD. sPD1 levels did not correlate with PSC. However, PSC in conjunction with AIH or IBD showed higher levels of sPD1. This suggests that T cell activation plays a critical role in active AIH and IBD but not in PSC. Soluble PDI levels could be used as a clinical biomarker to assess response in patients with AIH and for prospectively monitoring PSC patients for development of IBD or AIH.